Cognitive and embodied mapping of data: an examination of children’s spatial thinking in data physicalization - Zhu, Caiwei; Klapwijk, Remke; Silva-Ordaz, Miroslava; Spandaw, Jeroen; de Vries, Marc J. (Frontiers in Education, 2023)
Understanding and effectively using visual representations is important to learning science, technology, engineering, and mathematics (STEM). Various techniques to visualize information, such as two- and three-dimensional graphs, diagrams, and models, not only expand our capacity to work with different types of information but also actively recruit our visual-spatial thinking. Data physicalization is emerging as a beginner-friendly approach to construct information visualization. Mapping intangible data onto tangible artifacts that possess visual, spatial, and physical properties demands an interplay of spatial thinking and hands-on manipulation. Much existing literature has explored using formatted infographics to aid learning and spatial thinking development. However, there is limited insight into how children may leverage their spatial thinking to create information visualizations, particularly tangible ones. This case study documented the data physicalization activities organized in two design classrooms of an international school in the Netherlands, with 37 children aged 11 to 12. Seven themes relevant to spatial thinking were identified from multimodal evidence gathered from the data physicalization artifacts, classroom videos and recordings of children’s making process, and semi-structured interviews with children. Our findings suggested that these children generated various ideas to create visual-spatial forms for data with the materials at hand, such as mapping quantities to tangible materials of different sizes, using spatial ordinal arrangement, and unitizing materials to set visual parameters. Meanwhile, they evaluated and adjusted the visual-spatial properties of these materials according to the numerical data they had, crafting feasibility, and others’ spatial perspectives. What was particularly interesting in our findings was children’s iteration on their visual-spatial understandings of the intangible numerical values and the tangible materials throughout the embodied making processes. Overall, this study illustrated the different types of spatial thinking children applied to create their data physicalizations and offered insights into how embodied experiences accompanying the open-ended visualization challenge allowed children to explore and construct spatial understandings.